EFSA Health Claims-Based Virgin Olive Oil Shelf-Life - Vanessa Mancebo-Campos; Maria Desamparados Salvador; Giuseppe Fregapane (MDPI AG, 2023)
The consumption of extra virgin olive oil (EVOO) has been linked to various health benefits, including a reduced risk of cardiovascular disease. EVOO contains triglycerides and unsaturated fatty acids, as well as minor compounds, such as polar phenols and tocopherols, which play a crucial nutritional and biological role. The composition of these minor compounds is affected by various factors that distinguish EVOOs from lower-quality olive oils. The European Parliament approved Regulation 1924/2006 that governs the use of health claims on food products based on EFSA reports. Currently, there are several authorized health claims related to unsaturated fatty acids, vitamin E, and polyphenol content that can be used for commercial reasons on EVOO labels. Consumers can easily take enough grams of EVOO per day to receive the beneficial effects of the nutrient in question; nevertheless, the use of these health claims is subject to a required concentration of specific nutrients throughout the shelf life of olive oil. Few studies have examined the evolution of these compounds along the shelf life of EVOO to meet health claims. This work aims to evaluate the nutritional profile of several EVOOs with potential health claims and the evolution of related nutrients during storage in darkness at different temperatures. This study proposes an accelerated method to determine the end of the EVOO shelf life based on the loss of its nutraceutical capacity and the inability to comply with the stated health claims.